Stages of Development in a Holy Life - Kaempchen, Martin (Journal of Dharma, 1983)
The "Holy" has been a subject of discussion since the epoch making work by Rudolf Otto The Idea of the Holy. It investigates the existence of the "Holy" as manifest through the different cultural expressions of man. Otto's main contention is that the "Holy" is a quality which evokes irrational reactions in man. It cannot be entirely integrated into his consciousness, rather it will always stand apart as the "other", as a strange phenomenon which inspires "fear and trembling", but simultaneously attracts and fascinates. This is true for the Holy which manifests itself in places and auspicious times, in rituals and sacred scriptures, but also in persons. The recognition of holiness in a person is due to a man's peculiar faculty of "divination"; this, according to Otto, is man's faculty to intuitively "know" once he comes face to face with a holy person that he is, indeed, holy. Recognition of holiness depends on two conditions, namely, the recognizer must have an obscure a priori cognition of holiness; it should be implanted in him as a "category" of the mind. l Secondly, the holy person must project a definite aura of holiness around him which is, as Otto writes, the "peculiar power of his personality, the special impression he makes on the bystander" 2 Holiness thus is normally a discovery followed by "spontaneous responses of feeling,' '8 and a certain sudden awe. Otto goes to the extent of supposing that the recognition of holiness necessitates a kind of "congeniality"' of the person perceiving holiness and the holy person.